Pemetaan Jalur Jalan Wisata Bukit Jamur di Kabupaten Bengkayang Menggunakan Sistem Informasi Geografis (SIG) - Erni Yuniarti; Meta Indah Fitriani; Tita Khairiyah (Diponegoro University, 2021)
Bukit Jamur is located in a strategic area near Bengkayang Urban and is an urban tourism icon that is popular with visitors to do light-scale hiking. Although located near urban areas, there are no information boards so visitors are not aware of the existence of tourist sites and the lack of road directions both in the village and on the hiking trails. In addition, inadequate road infrastructure makes visitors feel uncomfortable. The delivery of information with a map is expected to make it easier for visitors to know the initial condition of the tourist location. The purpose of this research is to map the road to tourist sites equipped with road signs and information boards so that visitors can know the route clearly. The analysis method in this research uses the method of implementing Geographic Information System (SIG). The findings in the field stated that there are 2 village road paths, namely the Belangko Hamlet road and the Dusun Jaku Bawah road path that is still lacking road directions and there are 3 hiking paths, namely stairways cliff paths and weeds that have not been equipped with directions and information boards so that there needs to be additional directions and information boards in the village and climbing.